A comparison of circumgalactic Mg II absorption between the TNG50 simulation and the MEGAFLOW survey - DeFelippis, Daniel; Bouché, Nicolas F.; Genel, Shy; Bryan, Greg L.; Nelson, Dylan; Marinacci, Federico; Hernquist, Lars (The astrophysical journal, 2021)
The circumgalactic medium (CGM) contains information on gas flows around galaxies, such as accretion and supernova-driven winds, which are difficult to constrain from observations alone. Here, we use the high-resolution TNG50 cosmological magnetohydrodynamical simulation to study the properties and kinematics of the CGM around star-forming galaxies in 1011.5-1012 M ⊙ halos at z ≃ 1 using mock Mg ii absorption lines, which we generate by postprocessing halos to account for photoionization in the presence of a UV background. We find that the Mg ii gas is a very good tracer of the cold CGM, which is accreting inward at inflow velocities of up to 50 km s−1. For sight lines aligned with the galaxy’s major axis, we find that Mg ii absorption lines are kinematically shifted due to the cold CGM’s significant corotation at speeds up to 50% of the virial velocity for impact parameters up to 60 kpc. We compare mock Mg ii spectra to observations from the MusE GAs FLow and Wind (MEGAFLOW) survey of strong Mg ii absorbers (EW2796 Å 0 > 0.5 Å). After matching the equivalent-width (EW) selection, we find that the mock Mg ii spectra reflect the diversity of observed kinematics and EWs from MEGAFLOW, even though the sight lines probe a very small fraction of the CGM. Mg ii absorption in higher-mass halos is stronger and broader than in lower-mass halos but has qualitatively similar kinematics. The median-specific angular momentum of the Mg ii CGM gas in TNG50 is very similar to that of the entire CGM and only differs from non-CGM components of the halo by normalization factors of ≲1 dex.
Gesehen am 05.08.2022